Miniature DC-DC Boost Converter for Driving Display Panel of Notebook Computer - Seok-Hyeong Ham; Hyung-Jin Choe (Energies, 2019)
This paper proposes a miniature DC-DC boost converter to drive the display panel of a notebook computer. To reduce the size of the circuit, the converter was designed to operate at a switching frequency of 1 MHz. The power conversion efficiency improved using a passive snubber circuit that consisted of one inductor, two capacitors, and two diodes; it reduced the switching losses by lowering the voltage stress of the switch and increased the voltage gain using charge pumping operations. An experimental converter was fabricated at 2.5 cm × 1 cm size using small components, and tested at input voltage 5 V ≤ VIN ≤ 17.5 V and output current 30 mA ≤ IO ≤ 150 mA. Compared to existing boost converters, the proposed converter had ~7.8% higher power conversion efficiency over the entire range of VIN and IO, only ~50% as much voltage stress of the switch and diodes, and a much lower switch temperature TSW = 49.5 °C. These results indicate that the proposed converter is a strong candidate for driving the display panel of a notebook computer.